1958
DOI: 10.1111/j.1476-5381.1958.tb00197.x
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Dopamine on the Arterial Blood Pressure of the Guinea‐pig

Abstract: The depressor action of dopamine (8-3: 4-dihydroxyphenylethylamine) upon the arterial blood pressure of the guinea-pig has been studied. This effect begins without a latent period. It is often enhanced after the intravenous injection of iproniazid (Marsilid). The depressor response is sufficiently sensitive to serve as a method of bioassay of dopamine in microgram quantities. Observations on the depressor action of L-dopa have also been made. This effect is also enhanced by iproniazid; it begins after a latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

1961
1961
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 8 publications
1
9
0
2
Order By: Relevance
“…In some experiments this initial hypertension is followed by a prolonged increase or depression of blood pressure. The secondary fall of blood pressure caused by tyramine was similar to the blood pressure fall caused by dopamine in the guinea-pig (Hornykiewicz, 1958;Burn & Rand, 1958b). It was also found that the hypertensive effect of tyramine gradually diminished after repeated injections.…”
Section: Discussionsupporting
confidence: 53%
“…In some experiments this initial hypertension is followed by a prolonged increase or depression of blood pressure. The secondary fall of blood pressure caused by tyramine was similar to the blood pressure fall caused by dopamine in the guinea-pig (Hornykiewicz, 1958;Burn & Rand, 1958b). It was also found that the hypertensive effect of tyramine gradually diminished after repeated injections.…”
Section: Discussionsupporting
confidence: 53%
“…He showed it was resulting directly from dopamine and not a metabolite of dopamine that was responsible. He also tested l ‐dopa and found the same effect …”
Section: The Scientific Developments Underlying the Discovery Of Strimentioning
confidence: 74%
“…In short, my experiments fully confirmed Blaschko's notion of dopamine having some own functions in the body, independent of noradrenaline and adrenaline. 3 This was my first direct contact with dopamine. While writing up my experiments and ruminating on dopamine's own actions in the body (this was in the exceptionally hot Oxford summer of 1957) a short report in the August 3 issue of Nature attracted my special interest; it dealt with the occurrence of a new catechol compound in the brain, claiming that it actually was dopamine!…”
Section: )mentioning
confidence: 97%